2012
DOI: 10.1038/srep00577
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic Acid Enhances Caffeine-Induced Cell Death via Caspase-Independent Cell Death

Abstract: Caffeine is a globally consumed psychostimulant but can be fatal to cells at overdose exposures. Although caspase-dependent apoptosis plays a role in caffeine-induced cell death, the responsible intracellular signalling cascade remains incompletely understood. The cellular slime mould, Dictyostelium discoideum, does not possess caspase-dependent apoptotic machinery. Here, we observed that ablation of D. discoideum plaA, which encodes a phospholipase A2 (PLA2) homolog, leads to a decreased rate of cell death un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…On the other hand, caffeine had no effect on HUVECs differentiation on Matrigel or migration in vitro (data not shown). These results indicate that inhibitory effect of caffeine on angiogenesis is related, at least in part, to its apoptotic effect [50, 51]. …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, caffeine had no effect on HUVECs differentiation on Matrigel or migration in vitro (data not shown). These results indicate that inhibitory effect of caffeine on angiogenesis is related, at least in part, to its apoptotic effect [50, 51]. …”
Section: Discussionmentioning
confidence: 99%
“…Caffeine inhibits all adenylyl cyclases, viz., ACA, ACB, and ACG in Dictyostelium , and although the exact molecular mechanism of action remains unclear, this inhibition is neither due to ceasing of the secretion of the cAMP produced nor due to hyperactivation of cAMP phosphodiesterases [17] . We found here that the Dd Rbg-3 -null mutant exhibited a caffeine-resistant phenotype and was capable of producing cAMP under a physiologically effective caffeine concentration like cells lacking phospholipase A2 gene [27] , indicating that caffeine acts on adenylyl cyclase via Dd Rbg-3. Although we have yet to determine whether caffeine acts directly on Dd Rbg-3 or via other components, our results indicate that Dd Rbg-3 is involved in the caffeine-mediated inhibition of adenylyl cyclase activity.…”
Section: Discussionmentioning
confidence: 73%
“…This could be due to the presence of caffeine in the Arabica coffee extract. In a study that used mammalian cell line (CHO), caffeine has been found to exhibit acute cellular toxicity by inhibiting the growth and causing death to the cells (Kuwayama, 2012). In vivo study on the acute toxicity of caffeine was reported in animals such as fish (Leuciscus idus) with LC50 of 87 µg/mL after 96 h exposure, rats with LD50 of 200 -400 mg/kg, and mice with LD50 of 185 mg/kg (CCOHS, 2012).…”
Section: Discussionmentioning
confidence: 99%